Rainbow coloured dots and rebellious old ladies: The gurlesque in two contemporary Swedish comic books. Issue 3 (August 2018) - Österholm, Maria Margareta
The term gurlesque refers to an aesthetics that mixes feminism, femininity, the grotesque and the cute. This article explores how contemporary Swedish feminist comic books do gurlesque theory with the aim of contributing to the theoretical conversation about feminine aesthetics and gurlesque. The study focuses on two contemporary Swedish comic books, Jag är din flickvän nu ( I Am Your Girlfriend Now ) (2006) by Nina Hemmingsson and Allt kommer bli bra ( Everything Will Be Fine ) (2013) by Lisa Ewald. The article views gurlesque as a queer aesthetics, as a form of wilful misinterpretation and taunting of perceptions of femininity. The word gurlesque draws from the word 'girl', and questions the connection between girlhood and young age from a queer perspective. Although the gurlesque is rooted in images of girlhood, it has the potential to grasp femininities of all ages.